Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1165/rcmb.2020-0188tr
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP-Ribose) Polymerase Inhibition in Acute Lung Injury. A Reemerging Concept

Abstract: PARP1, the major isoform of a family of ADP-ribosylating enzymes, has been implicated in the regulation of various biological processes including DNA repair, gene transcription, and cell death. The concept that PARP1 becomes activated in acute lung injury (ALI) and that pharmacological inhibition or genetic deletion of this enzyme can provide therapeutic benefits emerged over 20 years ago. The current article provides an overview of the cellular mechanisms involved in the pathogenetic roles of PARP1 in ALI and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 106 publications
(93 reference statements)
2
14
0
Order By: Relevance
“…A candidate might be mitochondrial DNA, which has been detected in the EVLP perfusate of rat lungs (35), and in the BAL and plasma following LTx (36,37). Another possibility is that inflammation arises during EVLP independently from DAMP release, for example through the activation of the enzyme poly(ADP-ribose) polymerase (PARP), as recently proposed by our group (5,38), or could simply reflect the presence of endogenous inflammatory cells in the graft (39).…”
Section: Discussionmentioning
confidence: 88%
“…A candidate might be mitochondrial DNA, which has been detected in the EVLP perfusate of rat lungs (35), and in the BAL and plasma following LTx (36,37). Another possibility is that inflammation arises during EVLP independently from DAMP release, for example through the activation of the enzyme poly(ADP-ribose) polymerase (PARP), as recently proposed by our group (5,38), or could simply reflect the presence of endogenous inflammatory cells in the graft (39).…”
Section: Discussionmentioning
confidence: 88%
“…Resistance to inflammation has been observed in PARP1 knockout mice subjected to various forms of injury including reperfusion and inflammation [ 1 , 2 ]. Also, PARP1 activation plays a significant role in the pathogenesis of ARDS [ 27 , 28 , 29 ]. Pediatric patients with serious burn injuries reportedly presented with PARP1 activation, as demonstrated by increased PARylation in endothelial cells and leukocytes from muscle tissue [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PARP inhibitors (e.g., Olaparib and talazoparib) are known to have promising therapeutic efficacy in BRCA-associated breast cancers (Robson et al, 2017;Litton et al, 2018). Besides, the beneficial pharmacological effects of PARP inhibitors were observed on inflammatory diseases, such as liver inflammation and fibrosis (Mukhopadhyay et al, 2014), asthma (Zaffini et al, 2018), and acute and chronic mice lung injury (Szabo et al, 2020). Recently, Pantelidou et al revealed that interaction of PARP inhibition and STING/TBK1/IRF3 pathway activation regulates T cell recruitment and anti-tumor efficacy in cancer cells (Pantelidou et al, 2019).…”
Section: Discussionmentioning
confidence: 99%